The biogenesis and regulation of telomerase holoenzymes - Collins, Kathleen (2006)
Chromosome stability requires a dynamic balance of DNA loss and gain in each terminal tract of telomeric repeats. Repeat addition by a specialized reverse transcriptase, telomerase, has an important role in maintaining this equilibrium. Insights that have been gained into the cellular pathways for biogenesis and regulation of telomerase ribonucleoproteins raise new questions, particularly concerning the dynamic nature of this unique polymerase.